Clinical analysis of concurrent 3DCRT and XELOX treatment for postoperative local recurrence of rectal carcinoma in elderly patients - Zhuang, Baoxiong; Xu, Junyao; Xu, Kang; Wang, Jie (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Aim : To probe into the clinical effects of concurrent 3DCRT (3-dimensional conformal radiation therapy) and XELOX treatment for postoperative local recurrence of rectal carcinoma in the elderly patients. Material and methods : Fifty-seven elderly patients with postoperative local recurrence of rectal carcinoma were randomly divided into a clinical group and a control group. The clinical group had 31 patients, who received 6 MV X-ray 3DCRT, 2 Gy per time, 5 times every week. After radiotherapy for the total pelvis until target dose (DT) in tumor focus reached 40 Gy/20f, the tumor focus was intensified up to DT 60-64 Gy with 8 MV X-ray DT 20-24 Gy. During radiotherapy, the patients were treated with XELOX (oxaliplatin 85 mg/m 2 , dl, Xeloda 850 mg/m 2 , p.o. d1–14) for two periods. The control group had 26 patients, who were only treated with XELOX. Results: The responder rate (RR) of the clinical group was 87.1%. The survival rates within 1, 2 and 3 years were 67.7%, 51.6% and 41.9% respectively, which were higher than the control group (p < 0.05). However, the clinical group had significantly more 1st and 2nd degree myelosuppression and hand-foot syndrome. The symptoms were relieved after symptomatic treatment. Conclusions : Concurrent 3DCRT and XELOX treatment for postoperative local recurrence of rectal carcinoma in the elderly patients greatly improved short-term efficacy and survival rate within 1, 2 and 3 years, while the toxic effects also increased greatly, but could be withstood by most patients.